2016
DOI: 10.1109/tthz.2016.2630845
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Phonon Escape Time for NbN Hot Electron Bolometers by Using GaN Buffer Layers

Abstract: In this paper, we investigated the influence of the GaN buffer-layer on the phonon escape time of phonon-cooled hot electron bolometers based on NbN material and compared our findings to conventionally employed Si substrate. The presented experimental setup and operation of the HEB close to the critical temperature of the NbN film allowed for the extraction of phonon escape time in a simplified manner. Two independent experiments were performed at GARD/Chalmers and MSPU on a similar experimental setup at frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…For the modeling, the electron DOI: 10.1109/TTHZ.2019.2945203 , This paper has been published in IEEE Trans.THz,Sci.Technol. v.9, (2019) / Open Access 6 temperature Te is assumed to be equal to Tc [14], [21]. The phonon temperature (Tph =0.8 Te) was calculated using the system of two heat balance equations: electron-phonon and phonon-substrate [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the modeling, the electron DOI: 10.1109/TTHZ.2019.2945203 , This paper has been published in IEEE Trans.THz,Sci.Technol. v.9, (2019) / Open Access 6 temperature Te is assumed to be equal to Tc [14], [21]. The phonon temperature (Tph =0.8 Te) was calculated using the system of two heat balance equations: electron-phonon and phonon-substrate [32].…”
Section: Discussionmentioning
confidence: 99%
“…This approach was frequently utilized for HEB mixer studies, and its validity has been confirmed for NbN HEB mixers (see e.g. [14]). For MgB2 HEBs, the I(V)-curves under the optimal power 700 GHz, 1.6 THz, and 2.6 THz LOs have been confirmed to correspond well to the I(V) without an LO, but at a temperature close to Tc [22].…”
Section: B Noise and Gain Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Alternative buffer-layers or substrates that yield single crystal NbN films are MgO [17,18], SiC [19,20] and sapphire [21], however, the use of sapphire in waveguide applications is restricted due to its hardness and MgO as a thin buffer-layer on Si or lapped quartz substrates is hygroscopic and may lead to life-time issues in the active device. Moreover, they do not provide a good acoustic match to NbN thin films [22,23], and results in a reduced phonon transparency, which has a negative impact on the achievable IF bandwidth in phonon-cooled HEB devices.…”
Section: Introductionmentioning
confidence: 99%
“…For NbN SNSPDs, reducing β by choice of substrate could lead to improved detection efficiency at longer photon wavelengths [7]. Increasing β has already been shown as a promising route for improving the bandwidth of NbN hot electron bolometers [43], and phonon trapping has been shown to improve single-photon energy resolution in kinetic inductance detectors [44]. The same would improve SNSPD count rates [5].…”
mentioning
confidence: 99%